A Systematic Literature Review on Politically Connected Directors/CEOs and Financial Performance and Earnings Quality - Lim, Keh Yee; Mohd Sabrun, Ibrahim; Sharon Cheuk, Choy Sheung (2023)
The presence of political connected firms is widespread in global economy, triggering growing studies to investigate this issue in business operation. This study aims to provide a comprehensive systematic literature review of the existing literature on the impact of political connection in board of directors and top management team on firm performance. This study analyses the bibliometric data and conducts content analysis to identify the outcomes of the existing empirical studies in this research topic. Following PRISMA guidance, a sample of 52 studies between 2008 and 2023 from Scopus database were selected in this study. The results show that the interest on such research topic is in a growing trend. Chinese studies have dominated the samples due to the change of regulation. Additionally, majority of previous studies are conducted quantitatively with the use of secondary data, focusing on non-financial industry. Prior studies have shown mixed results on the impact of political connection on firm performance, indicating that it could be a double-edged sword to a firm. Finally, this study outlines future direction for further research, especially in methodological aspect.